Association between age and patients’ perceptions of safety in hospitals during the COVID-19 pandemic: A cross-sectional study - Ana Lúcia Schaefer Ferreira de Mello; Franciely Daiana Engel; Gabriela Marcellino de Melo Lanzoni; Caroline Cechinel-Peiter; Diovane Ghignatti Costa; José Luis Guedes dos Santos; Alacoque Lorenzini Erdmann; Chantal Backman (Clinical Epidemiology and Global Health)
Aim: This study aimed to explore patients' perceptions of factors contributing to patient safety during hospitalization for COVID-19, with a focus on differences among three distinct adult age groups. Methods: A cross-sectional study was conducted. Data were collected from 533 patients hospitalized with COVID-19 in nine Brazilian university hospitals between April and December 2021. Sociodemographics, health conditions, and the Patient Measure of Safety (PMOS) data were gathered via telephone interviews. Descriptive statistics and ANOVA were used to compare the mean scores across PMOS items, domains, and total scores by age groups (18–44; 45–64; and 65+ years). Results: Patients aged 45–64 years reported the highest perception of safety, while those aged between 18 and 44 years reported the lowest. Statistically significant differences in safety perceptions were observed across age groups. The younger adult group (18–44 years) reported lower overall PMOS scores, particularly in areas such as equipment, access to resources, and organization and care planning, compared to the middle-aged group. Younger adults were more critical of aspects including attentiveness to patient concerns, availability of health professionals, space, and equipment, teamwork skills, and information sharing between the healthcare team and patients. Conclusion: Perception of factors contributing to patient safety during the COVID-19 pandemic varied across different age groups. Understanding these differences can inform the development of targeted strategies to incorporate patient perspectives into hospital safety initiatives, indicators development, and research to improve patient safety in hospital settings.